A regulatory CD9+ B‐cell subset inhibits HDM‐induced allergic airway inflammation. Issue 11 (25th August 2015) - Braza, F.; Chesne, J.; Durand, M.; Dirou, S.; Brosseau, C.; Mahay, G.; Cheminant, M. A.; Magnan, A.; Brouard, S.
Abstract Background Exposure to respiratory allergens triggers airway hyperresponsiveness and inflammation characterized by the expansion of TH2 cells and the production of allergen specific IgE. Allergic asthma is characterized by an alteration in immune regulatory mechanisms leading to an imbalance between pro‐ and anti‐inflammatory components of the immune system. Aims Recently B cells have been described as central regulators of exacerbated inflammation, notably in the case of autoimmunity. However, to what extent these cells can regulate airway inflammation and asthma remains to be elucidated. Materials & Methods We took advantage of a allergic asthma model in mice induced by percutaneous sensitization and respiratory challenge with an extract of house dust mite. Results In this study, we showed that the induction of allergic asthma alters the homeostasis of IL‐10+ Bregs and favors the production of inflammatory cytokines by B cells. Deeper transcriptomic and phenotypic analysis of Bregs revealed that they were enriched in a CD9+ B cell subset. In asthmatic mice the adoptive transfer of CD9+ B cells normalized airway inflammation and lung function by inhibiting TH2‐ and TH17‐driven inflammation in an IL‐10‐dependent manner, restoring a favorable immunological balance in lung tissues. Indeed we further showed that injection of CD9+ Bregs controls the expansion of lung effector T cells allowing the establishment of a favorable regulatory T cells/effector T cells ratio in lungs. Conclusion This finding strengthens the potential for Breg‐targeted therapies in allergic asthma.